Brain death and care of the organ donor - Lakshmi Kumar (Wolters Kluwer Medknow Publications, 2016)
Brain death has specific implications for organ donation with the potential for saving several lives. Awareness on maintenance of the brain dead has increased over the last decade with the progress in the field of transplant. The diagnosis of brain death is clinical and can be confirmed by apnea testing. Ancillary tests can be considered when the apnea test cannot be completed or is inconclusive. Reflexes of spinal origin may be present and should not be confused against the diagnosis of brain death. Adequate care for the donor targeting hemodynamic indices and lung protective ventilator strategies can improve graft quality for donation. Hormone supplementation using thyroxine, antidiuretic hormone, corticosteroid and insulin has shown to improve outcomes following transplant. India still ranks low compared to the rest of the world in deceased donation. The formation of organ sharing networks supported by state governments has shown a substantial increase in the numbers of deceased donors primarily by creating awareness and ensuring protocols in caring for the donor. This review describes the steps in the establishment of brain death and the management of the organ donor. Material for the review was collected through a Medline search, and the search terms included were brain death and organ donation.